Temperature‐sensitive male sterility in rice determined by the roles of AGO1d in reproductive phasiRNA biogenesis and function. Issue 4 (17th September 2022) - Shi, Chuanlin; Zhang, Jie; Wu, Bingjin; Jouni, Rachel; Yu, Changxiu; Meyers, Blake C.; Liang, Wanqi; Fei, Qili
Summary: Phased secondary siRNAs (phasiRNAs) are broadly present in the reproductive tissues of flowering plants, with spatial–temporal specificity. However, the ARGONAUTE (AGO) proteins associated with phasiRNAs and their miRNA triggers remain elusive. Here, through histological and high‐throughput sequencing analyses, we show that rice AGO1d, which is specifically expressed in anther wall cells before and during meiosis, associates with both miR2118 and miR2275 to mediate phasiRNA biogenesis. AGO1d preferentially binds to miR2118‐triggered 21‐nucleotide (nt) phasiRNAs with a 5′‐terminal uridine, suggesting a dual role in phasiRNA biogenesis and function. Depletion of AGO1d causes a reduction of 21‐ and 24‐nt phasiRNAs and temperature‐sensitive male sterility. At lower temperatures, anthers of the ago1d mutant predominantly show excessive tapetal cells with little starch accumulation during pollen formation, possibly caused by the dysregulation of cell metabolism. These results uncover an essential role of AGO1d in rice anther development at lower temperatures and demonstrate coordinative roles of AGO proteins during reproductive phasiRNA biogenesis and function.